Review of the Phytochemical and Pharmacological Studies of the Genus Markhamia - Ibrahim, Mutiat Bolanle; Kaushik, Nutan; Sowemimo, Abimbola Adepeju; Odukoya, Olukemi A. (Pharmacognosy Reviews)
Natural product compounds obtained from medicinal plants have been great contributions in the discovery of numerous clinically useful drugs. Markhamia species have been reportedly used by many cultures in human and veterinary traditional medicines. The five identified species of Markhamia, that is, Markhamia lutea, Markhamia obtusifolia, Markhamia stipulata, Markhamia tomentosa, and Markhamia zanzibarica have been the subject of chemical investigations that have led to the characterization of their secondary metabolites. Plants of the genus with the identified phytoconstituents, including phenylpropanoid glycosides (PhGs), terpenoids, phytosterols, lignans, quinones, and flavonoids, have been claimed to possess antiviral, antifungal, antiprotozoal, analgesic, antiinflammatory, and cytotoxic activities. In vitro and in vivo pharmacological research studies have reported the validation of the medicinal properties of plants of this genus. The present review analyzes published data from the ethnomedicinal, phytochemical, and pharmacological studies of plants of the genus Markhamia.
Keywords: Ethnomedicine; ethnopharmacology; Markhamia; phytochemistry